Nits and pseudonits in Indian children: A dermoscopic perspective - Aakash Gupta; Balachandra S Ankad; Priyanka Jaju; Nicholas Roland Drago (Wolters Kluwer Medknow Publications, 2019)
Background: Hair casts or pseudonits are tubular accretions that are movable encircling the hair shafts of the scalp. It is commonly confused as head lice or pediculosis capitis, which is a common concern in pediatric age group. Hair casts are common in psoriasis, seborrheic dermatitis, and pityriasis amiantacea. This misdiagnosis is a reason of patient and physician anxiety. We attempted to evaluate significance of trichoscopy in differentiating nits and pseudonits and therefore a better treatment plan. Aims and Objective: To evaluate trichoscopic patterns in nits and pseudonits. Methodology: The study was conducted in a tertiary hospital. Ethical clearance and consent from patients were obtained. DermLite 3 with ×10 magnification was employed for trichoscopy. Tiny concretions on the hair shafts were examined with trichoscopy. Patterns were analyzed. Results: Totally, 25 patients were included in the study with 7 boys and 18 girls. The mean age was 9 years. Trichoscopy demonstrated cylindrical white sheaths (2-7 mm) encircling the hair shafts in 15 patients (60%). Forty percent of the patients showed pyriform-shaped translucent and yellowish structures (0.8 mm) attached to hair shafts. Based on the trichoscopy patterns, diagnosis of pseudonits and nits was made in former and latter groups, respectively. Conclusion: Trichoscopy plays an important role in differentiation of nits and pseudonits. Since nits are contagious, correct diagnosis is of utmost importance for better management. Thus, trichoscopy is a reliable diagnostic procedure in daily practice of dermatologists.